2013
DOI: 10.1111/tesg.12011
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Effects in Industrial Location Choices: Industry Characteristics and Urban Accessibility

Abstract: In this paper we study how neighbourhood‐related spillovers affect location choices of manufacturing firms at a local level. A spatial Dirichlet‐multinomial regression model is applied to 90,000 new establishments of the Spanish Mediterranean Axis. Empirical findings show that spatial spillovers play an important role, together with traditional explanatory factors, in driving decisions of companies. Their size and scope depends on two main issues, the specific characteristics of the manufacturing industry the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 15 publications
(25 reference statements)
1
6
0
Order By: Relevance
“…This is mainly because it might be too complex to estimate and interpret the spatial lag terms. In addition, it also helps to compare with the results of most studies that only consider the spatial lags of independent variables (Autant‐Bernard ; Alamá‐Sabater et al ; Artal‐Tur et al ). It is generally assumed that all spatially weighted independent variables share one common spatial parameter in most studies such as Alamá‐Sabater et al () and Artal‐Tur et al ().…”
Section: Study Area Model Setting and Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…This is mainly because it might be too complex to estimate and interpret the spatial lag terms. In addition, it also helps to compare with the results of most studies that only consider the spatial lags of independent variables (Autant‐Bernard ; Alamá‐Sabater et al ; Artal‐Tur et al ). It is generally assumed that all spatially weighted independent variables share one common spatial parameter in most studies such as Alamá‐Sabater et al () and Artal‐Tur et al ().…”
Section: Study Area Model Setting and Variablesmentioning
confidence: 99%
“…Alamá‐Sabater et al () investigated the role played by spatial spillovers in location choices of firms in the Spanish region of Murcia. Artal‐Tur et al () studied how the location decisions of manufacturing firms are influenced by inter‐site spillovers at a local scale and found that spatial spillovers do play an important role. Daniel and Arauzo‐Carod () analysed the role of spatial effects in the industrial location process in Catalonia, Spain.…”
Section: Intra‐urban Firm Location: General Determinants and Spatial mentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas Artal‐Tur et al . ( ) and Risselada et al . () estimate discrete choice models, Cieślik () and Martínez et al .…”
mentioning
confidence: 85%
“…In particular, the papers included in this special issue analyse questions related to the regional determinants of foreign direct investments (Cieślik ), the role of spatial spillovers (Artal‐Tur et al . , Martínez et al . ), and the micropolitan analysis of relocations (Risselada et al ., ).…”
mentioning
confidence: 95%